Clinical research resource support for off‐site research coordinators in intensive and specialty care units - Ismael Castaneda; Karen Marder; Sudha Kashyap; Michael Rosenbaum (Wiley, 2023)
Abstract Clinical Research Coordinators (CRCs) are vital collaborators in a clinical research project. They often are the primary liaisons between investigators and human participants in studies and are involved in every aspect of many protocols, including participant recruitment, care (both usual medical care and specific study‐related monitoring and procedures), data collection, specimen processing, and follow‐up. The Clinical Translational Science Award program, which was created by the National Institutes of Health in 2006, has significantly expanded the venues in which Clinical Research Resource (CRR) - based CRCs are embedded. CRCs functioning in these areas, outside of the research‐focused in‐patient environment of the CRR, are designated as "off‐site" CRCs. Many of these locations, such as intensive care units and emergency departments, require that CRCs interact regularly with healthcare providers whose primary functions are focused on providing optimal patient care rather than research and often involving very complex patients. These off‐site CRCs require additional training and support outside of the usual research‐oriented environment of the CRR. They are required to function within the context of the patient‐care team while fostering implementation of collaborative research. This is a description of such a program specifically geared to off‐site CRCs with the goal of enhancing the quality of research and experiences of CRCs.